2004
DOI: 10.1097/01.pep.0000113272.34023.56
|View full text |Cite
|
Sign up to set email alerts
|

Interrater Reliability of Early Intervention Providers Scoring the Alberta Infant Motor Scale

Abstract: The AIMS manual provides sufficient information to attain high interrater reliability without training, but revisions regarding scoring are strongly recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 11 publications
2
30
0
Order By: Relevance
“…The latter was converted to an age-corrected z score based on a Belgian standardization group because the original norm reference values of the AIMS are not representative for the Belgian population anymore (De Kegel et al 2013). High inter-rater and test-retest reliability and concurrent validity are reported (Piper & Darrah 1994;Jeng et al 2000;Blanchard et al 2004;Snyder et al 2008).…”
Section: Methodsmentioning
confidence: 97%
“…The latter was converted to an age-corrected z score based on a Belgian standardization group because the original norm reference values of the AIMS are not representative for the Belgian population anymore (De Kegel et al 2013). High inter-rater and test-retest reliability and concurrent validity are reported (Piper & Darrah 1994;Jeng et al 2000;Blanchard et al 2004;Snyder et al 2008).…”
Section: Methodsmentioning
confidence: 97%
“…Subjects who scored less than 41 on the TIMSPI were then evaluated using The Children's Hospital of Philadelphia Infant Test for Neuromuscular Disorders (CHOP‐INTEND) which is a validated 16‐item, 64‐point scale shown to be reliable in SMA type 1 subjects 19, 24. Subjects scoring 41 or greater on the TIMPSI were evaluated using the Alberta Infant Motor Scale (AIMS), a 58‐item observational scale developed to assess motor development in children from birth until independent walking 25, 26…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with the PROP study protocol, we did not provide definitions or examples of abnormal findings. Standardized definitions of examination findings can improve interobserver agreement in multicenter studies, 30,31 but these may be used infrequently in studies that include respiratory examination findings as outcomes. A systematic review of pediatric drug and vaccine trials that included wheeze as an adverse event reported that only 26% of the trials provided a definition of wheezing.…”
Section: Discussionmentioning
confidence: 99%